Features of achievement in Surat Al-Ikhlas - Shaeen, Ranya Ahmed (Journal of Humanities & Social Sciences, 2021)
This research studies the achievement features in Surat Al-Ikhlas, the efficacy of the deliberative mechanism in studying the Qur’anic text, the effect of deliberative aspects in highlighting the content of the text in general, and the power of verbal actions in reinforcing this meaning. And it’s appeared that the Quranic hierarchy in Surat Al-Ikhlas. In order to prove the uniqueness and immortality of God, and in response to all the absurdities and delusions of God, the surah came with its four verses. To prove that the Qur’anic miracle is able to prove this, the award-winning belt published a portfolio of one hundred attributes of the Qur’an, for the attributes of God, and its denial for all. Slander and falsehood.